Pancasila Economy: Study Theory And Implementation In Economic Education In Indonesia - Agussalim Agussalim; Hartoyo Hartoyo; Wahyuni Wahyuni (Universitas Islam Negeri Sultan Syarif Kasim Riau Pekanbaru, 2022)
Pancasila economy is an economic system that is guided by the implementation of Pancasila. Pancasila Economic values must be instilled in the hearts and minds of the nation's children through economic education. This study aims to examine the Theory of Pancasila Economics and its implementation in economic learning in Indonesia. This research belongs to descriptive qualitative and quantitative research. Qualitative data includes the opinions of economists referred to in textbooks and journal articles published online. Quantitative data from questionnaires on the understanding and implementation of Pancasila values in economic learning. The conclusion of the research on Pancasila Economics as an economic science with a new paradigm that was born from the condition of economic scholarship in Indonesia is hegemonized by western thought. Likewise, the application of economic learning is dominated by neoclassical-capitalist economic theories which are irrelevant to the ideology of the Indonesian nation.